Effect of Montmorrilonite on the Chloroprene/Natural Rubber Blend - hesty eka mayasari; agung yanuar wirapraja (Balai Riset Dan Standardisasi Industri Surabaya, 2021)
The effect of montmorillonite on chloroprene (CR)/ natural rubber (NR) blend was studied in this research. Montmorillonite was used as a compatibilizer with the various amounts (0, 2.5, 5, 7.5, 10 phr). The compounds were done by the two-roll mill and hydraulic press. The cure characteristics, mechanical properties, morphology, and thermal characteristics had been investigated by rheometer, tensile strength tester, scanning electron microscope (SEM), and differential scanning calorimetry (DSC). The montmorillonite resulted in longer scorch time and lower activation energy. Analysis of the blends by SEM and DSC showed that montmorillonite resulted in a compatible blend. The 2.5 phr montmorillonite gave the best curing characteristics with the lowest optimum time, the highest constant rate, and the lowest activation energy. It also gave the best tensile strength, elongation, and tear strength. The 2.5 phr montmorillonite was the proper compatibilizer for CR/NR blend